(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2022)
The expenditures of the general budget, in its operational and investment divisions, are a basic factor in the economic and social growth of any country, and its impact on various economic activities such as income, employees , and the standard of living of members of society. This was based on a basic premise: Does increasing or decreasing investment expenditures have an effect on increasing or decreasing the tax proceeds, What is the level of relationship between them? and to achieve the goal of the research, an inductive and analytical method was chosen to measure the impact of the investment budget expenditures on the tax outcome quantitatively using the financial data obtained from The General Authority for Taxes, Ministry of Finance and Ministry of Planning.